Inhibition of Aldehyde Dehydrogenase-Activity Expands Multipotent Myeloid Progenitor Cells with Vascular Regenerative Function. (12th February 2018) - Cooper, Tyler T.; Sherman, Stephen E.; Kuljanin, Miljan; Bell, Gillian I.; Lajoie, Gilles A.; Hess, David A.
Abstract : Blood-derived progenitor cell transplantation holds potential for the treatment of severe vascular diseases. Human umbilical cord blood (UCB)-derived hematopoietic progenitor cells purified using high aldehyde dehydrogenase (ALDH hi ) activity demonstrate pro-angiogenic functions following intramuscular (i.m.) transplantation into immunodeficient mice with hind-limb ischemia. Unfortunately, UCB ALDH hi cells are rare and prolonged ex vivo expansion leads to loss of high ALDH-activity and diminished vascular regenerative function. ALDH-activity generates retinoic acid, a potent driver of hematopoietic differentiation, creating a paradoxical challenge to expand UCB ALDH hi cells while limiting differentiation and retaining pro-angiogenic functions. We investigated whether inhibition of ALDH-activity during ex vivo expansion of UCB ALDH hi cells would prevent differentiation and expand progeny that retained pro-angiogenic functions after transplantation into non-obese diabetic/severe combined immunodeficient mice with femoral artery ligation-induced unilateral hind-limb ischemia. Human UCB ALDH hi cells were cultured under serum-free conditions for 9 days, with or without the reversible ALDH-inhibitor, diethylaminobenzaldehyde (DEAB). Although total cell numbers were increased >70-fold, the frequency of cells that retained ALDH hi /CD34+ phenotype was significantly diminished under basal conditions. In contrast, DEAB-inhibition increased total ALDH hi /CD34+ cell number by ≥ 10-fold, reduced differentiation marker (CD38) expression, and enhanced the retention of multipotent colony-forming cells in vitro. Proteomic analysis revealed that DEAB-treated cells upregulated anti-apoptotic protein expression and diminished production of proteins implicated with megakaryocyte differentiation. The i.m. transplantation of DEAB-treated cells into mice with hind-limb ischemia stimulated endothelial cell proliferation and augmented recovery of hind-limb perfusion. DEAB-inhibition of ALDH-activity delayed hematopoietic differentiation and expanded multipotent myeloid cells that accelerated vascular regeneration following i.m. transplantation in vivo. Abstract : Inhibition of aldehyde dehydrogenase activity limits hematopoietic progenitor cell differentiation and enhances the expansion of UCB ALDH hi progeny with vascular regenerative function.